Measures of Bilingual Cognition – From Infancy to Adolescence. Issue 1 (26th August 2021) - Williams, Lindsay; Parthasarathy, Prasiddha; Molnar, Monika
An extensive literature exists regarding the effect of bilingualism on cognition in developing populations. However, the term 'cognition' is vague and applies to a large number of different abilities. We reviewed 60 publications examining cognition in simultaneous bilingual children to understand what aspects of cognition have been studied in this population and what tasks have been used, in addition to qualitatively assessing the results of bilingual/monolingual comparisons. Executive function was the most frequently assessed cognitive ability across all age groups, paralleling the adult bilingual literature, with memory flexibility and theory of mind also emerging as common targets within infant and preschool age groups. Results are discussed in light of developmental trajectories and assessment methodologies currently available for the cognitive abilities represented in this literature.